Analisis Pengaruh Laju Pertumbuhan Penduduk, Rasio Ketergantungan dan Indeks Pembangunan Manusia Terhadap Pertumbuhan Ekonomi di Kota Banjarmasin - Lisa Agustin; Muhammad Rusmin Nuryadin (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This study aims : to determine the effect and relationship of population growth rate, dependency ratio and human development index (HDI) on economic growth in Banjarmasin City. This study uses quantitative research by using numerical and statistical data analysis methods, to obtain significant results from the relationship between the independent variables and the dependent variable under study.The data analysis method used in this study is multiple linear regression analysis and uses the eviews application as a data analysis tool. The results of this study indicate that the variable population growth rate has a significant and positive correlation to the economic growth of Banjarmasin City. While the dependency ratio variable has a significant and negative correlation to the economic growth of Banjarmasin City.